1868 Ark. Acts 218, Acts of the General Assembly of Arkansas, § 12 - (:unkn) unknown (General Publisher, 1868)
Any person who threatens or draws a pistol, gun, or other deadly weapon upon a sheriff or other officer executing a civil or criminal process shall be deemed guilty of a felony, imprisoned in the pentitentiary not less than one nor more than five years.
--
Keywords: BRANDISHING